Pengaruh Digital Marketing melalui TikTok terhadap Pemasaran Produk UMKM di Cicarimanah - Husnulmar’ati, Ghina; Firmansyah, Esa; Helmiawan, Muhammad Agreindra (Jurnal Teknologi Riset Terapan, 2025)
Purpose: The purpose of this study is to understand how using TikTok as a digital marketing platform can help Micro, Small, and Medium Enterprises (MSMEs) in Cicarimanah Village, Situraja District, Sumedang Regency to improve their product marketing. The study aims to see whether TikTok can increase brand awareness, customer interaction, and product sales. Methodology/approach: This research uses a quantitative approach. Data were collected through surveys, interviews, and direct observations of MSME owners who actively use TikTok for marketing their products. The study was conducted specifically in Cicarimanah Village, Situraja District, Sumedang Regency, and focused on local MSMEs that utilize TikTok as part of their marketing efforts. No specific software or brand tools were mentioned, but the TikTok platform was central in the data collection and analysis process. Results/findings: The findings show that using TikTok for digital marketing has a positive effect on MSMEs. It helps in increasing brand awareness, improving customer engagement, and boosting product sales. TikTok allows MSMEs to promote their products in a creative, interactive, and effective way. Conclusion: TikTok has strong potential as a marketing tool for UMKM in Cicarimanah. Its effective use requires digital skills, creative content, platform integration, and data-driven strategies to support brand growth and business development. Limitations: The study is limited to MSMEs in one village only, so the results may not represent MSMEs in other regions or sectors. Also, the study does not explore long-term impacts or compare TikTok with other digital marketing platforms Contribution: This research contributes to the field of digital marketing and entrepreneurship development, especially for rural MSMEs. It provides practical insights for small business owners, marketing practitioners, and policymakers on how social media particularly TikTok can be used as a low-cost and high-impact marketing tool to help MSMEs grow and reach wider audiences.